Business in Multicultural Environment - Nguyen, Thi Minh Huyen (Khoa Quốc tế, ĐHQGHN, 2020)
This course provides a cohesive overview of the role of culture in conducting global business and the management issues influenced by differences in cultures. Thus, it will address differences in attitudes, values and beliefs among peoples with different cultural background that have a huge influence on managers and management practice and on how organizations can cultivate a global mindset among its workforce. The course content is relevant to all individuals who will be engaged in the general management of people and are applicable to all types of jobs within all organizations and industries.